Evaluation of a rapid colorimetric field test to assess the effective life of long-lasting insecticide-treated mosquito nets in the Lao PDR - Green, MD; Mayxay, M; Beach, R; Pongvongsa, T; Phompida, S; Hongvanthong, B; Vanisaveth, V; Newton, P; Vizcaino, L; Swamidoss, I (BioMed Central, 2013)
BACKGROUND: Malaria morbidity and mortality have been significantly reduced through the proper use of insecticide-treated mosquito nets, but the extra protection afforded by the insecticide diminishes over time. The insecticide depletion rates vary according to location where wash frequency and wear are influenced by cultural habits as well as the availability of water. Monitoring of available insecticides on the net surface is essential for determining the effective life of the net. Therefore, a rapid and inexpensive colorimetric field test for cyanopyrethroids (Cyanopyrethroid Field Test or CFT) was used to measure surface levels of deltamethrin on insecticide-coated polyester nets (PowerNets™) in rural Lao PDR over a two-year period. METHODS: Net surface levels of deltamethrin were measured by wiping the net with filter paper and measuring the adsorbed deltamethrin using the CFT. A relationship between surface levels of deltamethrin and whole net levels was established by comparing results of the CFT with whole levels assayed by high-performance liquid chromatography (HPLC). An effective deltamethrin surface concentration (EC80) was determined by comparing mosquito mortality (WHO Cone Test) with CFT and HPLC results. Five positions (roof to bottom) on each of 23 matched nets were assayed for deltamethrin surface levels at 6, 12, and 24 months. Mosquito mortality assays (WHO Cone Tests) were performed on a subset of eleven 24-month old nets and compared with the proportion of failed nets as predicted by the CFT. RESULTS: At six months, the nets retained about 80% of the baseline (new net) levels of deltamethrin with no significant differences between net positions. At 12 months, ~15-40%, and at 24 months <10% of deltamethrin was retained on the nets, with significant differences appearing between positions. Results from the CFT show that 93% of the nets failed (deltamethrin surface levels </= EC80) at 24 months. This value is in agreement with 91% failure as determined by the WHO Cone Test on a subset of 11 nets. The CFT results show that 50% of the nets from Laos failed at 12 months of normal use. CONCLUSION: The CFT is a useful and accurate indicator of net efficacy and may be substituted for mosquito bioassays.